Fracture of Two Moderately Cross-Linked Polyethylene Tibial Inserts in a TKR Patient - Matthew G. Teeter; James P. McAuley; Douglas D. Naudie (Case Reports in Orthopedics)
Highly cross-linked polyethylene has become the gold standard in total hip replacement for its wear resistance. Moderately crosslinked polyethylene is now available for total knee replacement (TKR), although concerns about reduced mechanical strength have prevented widespread adoption. The purpose of this report is to describe an unusual case where a patient underwent cruciate retaining TKR using a moderately crosslinked polyethylene tibial insert that went on to fracture twice in the same location across the primary and first revision surgery. The first tibial insert was 10 mm thick and was implanted for 16 months. The second tibial insert was 15 mm thick and was implanted for 11 months. Both fractured along the posterior aspect of the medial articular surface. The lack of a specific event leading to these fractures and the fact that they occurred twice in the same location in the same patient suggest that caution is still necessary regarding the introduction of crosslinked polyethylene for TKR surgery.